Point last seen [large type] - Dodd, Christina (Wheeler Publishing, a part of Gale, a Cengage Company, 2022)
"When Adam Ramsdell pulls Elle's half-frozen body from the surf on a California beach, she has no memory of what her full name is and how she got those bruises ringing her throat. Elle finds refuge in Adam's home on the edge of Gothic, a remote village located between the steep lonely mountains and the raging Pacific Ocean. As flashes of her memory return, Elle faces a terrible truth--buried in her mind lurks a secret so dark it could get her killed. Everyone in Gothic seems to hide a dark past. Until Elle can unravel the truth, she doesn't know who to trust, when to run, and who else might be hurt when the killer who stalks her nightmares appears to finish what he started"--